RANCANG BANGUN APLIKASI BIOINFORMATIKA BIOKIBA MENGGUNAKAN BIOPYTHON DAN FRAMEWORK LAMINAS - Edrian Hadinata (Jurnal Abdi Ilmu, 2021)
Currently, there are various emerging applications of bioinformatics that can make it easier for biological researchers to be able to analyze DNA and RNA sequences. Biological applications such as Biopython are open source module-based applications that can be combined with other programs for free. Many web-based applications have also been developed because they are considered easier than desktop applications because they are portable in addition to being easier to integrate with central bioinformatics data around the world. Laminas Framework which carries the MVC concept and is based on object-oriented programming and with its advantages fits the pattern of bioinformatics application development. The hybrid process between the system architecture contained in the framework and business processes in bioinformatics is a challenge for researchers. The process of data communication and execution of shell commands that are triggered in the middleware and continuously connected to the data source makes the process faster. The results of testing the laminas framework through the phpunit test contained in the laminas framework can be tested well and the python module that is formed is tested with pytest and unittest displays good results. so that structured and flexible bioinformatics applications can be developed further.